Sound-absorbing panel structure

Through the multi-layered cement sound-absorbing panel, combined with polyvinyl alcohol and cellulose nanofibers, a porous structure is formed, which solves the problem of insufficient sound absorption rate of existing cement sound-absorbing materials in the low and high frequency ranges, and achieves an efficient and lightweight sound-absorbing effect.

JP2025018001AActive Publication Date: 2025-02-06TANAKA CONSTR CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023121364
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06
Estimated Expiration
2043-07-26

AI Technical Summary

Technical Problem

The existing cement sound absorbing materials have insufficient sound absorption rate in the low and high frequency ranges, and there are problems with manufacturing and strength structure, which is difficult to meet the practical application needs.

Method used

A cement sound-absorbing panel with a multi-layer structure includes a surface layer, a back layer and a middle void layer. The surface layer is composed of polyvinyl alcohol and cellulose nanofibers. The back layer is composed of cement and cellulose nanofibers. The intermediate layer forms multiple holes through the cover layer, which connects with the surface layer, enhancing the strength and sound-absorbing performance of the panel.

Benefits of technology

The sound absorption rate of the panel in the wide frequency range is improved, the weight is reduced, and frequency dependence is optimized by adjusting the porosity and hole structure, and the efficient sound absorption effect is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018001000001_ABST
    Figure 2025018001000001_ABST
Patent Text Reader

Abstract

To provide a cement sound-absorbing panel structure which has improved sound absorption coefficient over a wide frequency range from low to high frequencies and is lightweight.SOLUTION: The sound-absorbing panel structure of the present invention is a sound-absorbing panel structure in which a plurality of sound-absorbing panel materials 1 are arranged, the sound-absorbing panel material 1 having a surface layer 10 made of cement containing PVA and CNF, a back layer 20 made of cement or cement containing CNF, a void layer 30 formed by covering the front and back sides of a layered body 31 arranged between the surface layer 10 and the back layer 20 and having a plurality of voids formed therein with laminated sheets 32 and 33, and a plurality of small holes 40 formed from the surface layer 10 to reach the void layer 30 and communicate with all of the voids. A plurality of types of sound-absorbing panel materials with different sound-absorbing characteristics are arranged.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cement sound absorbing panel structure having sound absorbing properties suitable for buildings. [Background technology]

[0002] Cement compositions such as mortar or concrete are mainly used as structural materials in the civil engineering and architectural fields, but are also incorporated into buildings as functional materials other than structural materials. In recent years, concrete buildings have been constructed in urban office districts, and buildings such as buildings are lining both sides of roads. As a result, noise from vehicles traveling on the roads reverberates and spreads on the walls of buildings, causing noise problems. To address this problem, various soundproof walls have been proposed.

[0003] As described in Patent Document 1, the inventors have proposed a cement sound-absorbing material comprising a surface layer whose main component is cement and which contains cellulose nanofibers, an intermediate layer whose main component is cement and which contains cellulose nanofibers and polyvinyl alcohol, and a film-like air bubble sheet that is laminated on the intermediate layer and has numerous protruding voids that seal air in them, with numerous small holes formed from the surface layer on one side to the air bubble sheet.

[0004] Patent Document 2 describes a porous concrete sound absorbing material with sound absorbing properties that has continuous voids inside using coarse aggregates of different particle sizes as a sound absorbing material used in sound insulation walls installed along roads, etc. Patent Document 3 describes a sound insulation board in which a sound absorbing board made of a material containing inorganic wood chips in concrete is reinforced and fixed with a honeycomb structure. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6910678 [Patent Document 2] Patent No. 4303446 [Patent Document 3] JP 2015-55103 A Summary of the Invention [Problem to be solved by the invention]

[0006] Although the cement sound-absorbing material described in Patent Document 1 has achieved an improvement in sound absorption rate, there is still room for improvement in sound absorption level and frequency dependency for practical use. The sound-absorbing material described in Patent Document 2 also has problems in practical use in terms of manufacturing and strength of the void structure, and the sound-absorbing board described in Patent Document 3 is insufficient in terms of sound absorption rate for practical use.

[0007] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a cement sound-absorbing panel structure which has improved sound absorption coefficient over a wide frequency range from low to high frequencies and is lightweight. [Means for solving the problem]

[0008] The sound-absorbing panel structure of the present invention is a sound-absorbing panel structure in which a plurality of sound-absorbing panel materials are arranged, the sound-absorbing panel materials having a surface layer made of cement containing polyvinyl alcohol and cellulose nanofibers, a back layer made of cement or cement containing cellulose nanofibers, a void layer arranged so as to be laminated between the surface layer and the back layer and configured by covering the surface and back sides of a layered body in which a plurality of voids are formed with a laminated sheet, and a plurality of small holes formed from the surface layer to reach the void layer and communicate with all of the voids, and a plurality of types of the sound-absorbing panel materials having different sound-absorbing characteristics are arranged. Effect of the Invention

[0009] By having the above-mentioned configuration, the present invention is lightweight and is composed of an arrangement of multiple types of sound-absorbing panel materials with different sound-absorbing characteristics, so it is possible to realize a lightweight sound-absorbing panel structure with improved sound absorption rate over a wide frequency range. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a partially enlarged cross-sectional view of a sound-absorbing panel material used in an embodiment according to the present invention. [Diagram 2] FIG. 2 is an external perspective view of a core material. [Diagram 3] FIG. 2 is a partially enlarged cross-sectional view of an embodiment of a sound-absorbing panel material using a core material. [Figure 4] FIG. 2 is an enlarged cross-sectional view of another embodiment of the sound-absorbing panel material. [Diagram 5] FIG. 2 is an enlarged cross-sectional view of another embodiment of the sound-absorbing panel material. [Figure 6] FIG. 13 is an external perspective view of another embodiment of a sound-absorbing panel material. [Figure 7] FIG. 2 is an explanatory diagram relating to the manufacturing process of the sound-absorbing panel material. [Figure 8] FIG. 2 is an explanatory diagram of a sound-absorbing panel structure in which sound-absorbing panel materials are arranged. [Figure 9] 1 is a graph showing measurement results for the sound-absorbing panel materials of Examples 1 and 2 and a sound-absorbing panel structure in which these sound-absorbing panel materials are combined and arranged. [Figure 10] 1 is a graph showing measurement results for a sound-absorbing panel structure in which the sound-absorbing panel materials of Examples 3 to 5 are arranged. [Figure 11] 1 is a graph showing the measurement results for a sound-absorbing panel structure in which the sound-absorbing panel material of Example 2 and the sound-absorbing panel materials of Examples 3 to 5 are combined and arranged. [Figure 12] 1 is a graph showing the results of measuring the reverberation time for the sound-absorbing panel materials of Examples 2 and 4 and for a sound-absorbing panel structure in which these sound-absorbing panel materials are combined and arranged. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present invention will be described with reference to the drawings. Note that the embodiments described below are preferred examples for carrying out the present invention, and therefore various technical limitations are imposed thereon, but the present invention is not limited to these embodiments unless otherwise specified in the following description to the effect that the present invention is limited thereto.

[0012] Fig. 1 is a partially enlarged cross-sectional view of a sound-absorbing panel material used in a sound-absorbing panel structure according to the present invention. The sound-absorbing panel structure is constructed by arranging multiple types of sound-absorbing panel materials with different sound-absorbing properties, which will be described later, and can be constructed as soundproofing equipment by arranging the sound-absorbing panel materials in a planar manner on the walls and ceilings of buildings, or in a planar manner on structures such as exterior walls and sound insulation walls.

[0013] The sound-absorbing panel material 1 comprises a surface layer 10 made of cement containing polyvinyl alcohol and cellulose nanofibers, a back layer 20 made of cement or cement containing cellulose nanofibers, a void layer 30 arranged so as to be laminated between the surface layer 10 and the back layer 20 and constructed by covering the front and back sides of a layered body 31 in which a number of voids are formed with laminated sheets 32 and 33, and a number of small holes 40 formed from the surface layer 10 to reach the void layer 30 and communicate with all of the voids.

[0014] At the peripheral portion of the sound-absorbing panel material 1, cement made of the same material as the front layer 10 or the back layer 20 is formed to surround the periphery of the air gap layer 30 by a predetermined width, so that the air gap layer 30 is embedded inside the sound-absorbing panel material 1. This increases the strength of the sound-absorbing panel material 1, and by fixing the peripheral portion of the sound-absorbing panel material 1 to form a sound-absorbing panel structure, it becomes possible to improve the strength and durability of the sound-absorbing panel structure. The thickness of the sound-absorbing panel material is preferably set to 20mm to 50mm, and the density is set to 1.2 to 1.6 to reduce the weight.

[0015] The cement used in the front and back layers may be mortar or concrete, with mortar being preferred in terms of weight reduction. In the following description, a specific example using mortar will be described in detail.

[0016] <About the surface layer> The surface layer 10 preferably has a thickness of 5 mm to 15 mm. If the thickness is less than 5 mm, the sound absorbing effect becomes insufficient, and if the thickness is more than 15 mm, the depth (length) of the small holes becomes large, resulting in a decrease in strength.

[0017] The raw materials used for the surface layer 10 are mainly cement, fine aggregate such as sand, and polyvinyl alcohol (hereinafter abbreviated as "PVA"), with cellulose nanofibers (hereinafter abbreviated as "CNF") added.

[0018] The cement is preferably ordinary Portland cement, and from the viewpoints of compressive strength, tensile strength and fluidity, the mineral composition is preferably 45% to 55% by mass of C3S (alite), 15% to 25% by mass of C2S (belite), 5% to 10% by mass of C3A (aluminate phase), and 8% to 10% by mass of C4AF (ferrite phase).When incorporating a reinforcing material such as a mesh-like three-dimensional structure, in order to ensure fluidity for easily filling the inside of the reinforcing material, it is more preferable to use a composition with a reduced amount of the C3A component that promotes setting.

[0019] PVA is a saponified polyvinyl acetate, and has the characteristics of being highly hydrophilic and soluble in warm water. Many types of PVA have been developed to suit different applications, but in the present invention, the partially saponified type is preferred.

[0020] The mixing ratio of PVA to cement is preferably 1.0% to 15.0% by mass. If it is less than 1.0% by mass, it becomes difficult to express the elastic properties that make it easy to deform, and if it is more than 15.0% by mass, the swelling action becomes significant and the dimensional stability decreases. CNF is an extremely fine fiber material in which cellulose molecules are arranged in a linear chain, and is made by chemically and mechanically processing wood fibers obtained from wood or plant fibers to nano-size (10 -9 CNF is a biomass material that has been finely untangled to a size of 100 mm. It is also known that CNF can be dispersed in water to form a three-dimensional network structure, and has many excellent properties such as high strength, high elastic modulus, low linear expansion coefficient, high transparency, and gas barrier properties. It also has the advantage of being lightweight and reducing the environmental burden during production and disposal, and research and development is being conducted on its application in various fields.

[0021] The mixing ratio of CNF to cement is preferably 0.01% by mass to 0.1% by mass, in view of the balance between the expression of elastic properties by PVA and strength.

[0022] When producing CNF, the raw material used, such as wood chips, is pulped, and then further refined by known processes such as mechanical processing, TEMPO oxidation, and water jet processing, and formed into a slurry or powder form for use. Those refined by the underwater counter collision method (ACC method) have different characteristics derived from the raw material, and for example, pulp made from coniferous trees is preferred because it can achieve high strength. In addition, when TEMPO oxidation is performed, nanofibers with uniform fiber width are obtained, which is preferred in terms of high strength.

[0023] As aggregate for cement, known fine aggregate such as sand can be used. In the case of fine aggregate such as sand, it is advisable to use a size in which all the holes pass through a 10 mm sieve and 85% or more pass through a 5 mm sieve.

[0024] The water to be mixed with the cement and the curing water can be tap water, and it is preferable to add 5% to 15% by mass.

[0025] Examples of the admixture to be added include water reducing agents. Examples of water reducing agents include lignin-based, naphthalenesulfonic acid-based, aminosulfonic acid-based, and polycarboxylic acid-based water reducing agents, high-performance water reducing agents, and high-performance AE water reducing agents. Although the water reducing ability of high-performance water reducing agents is improved by increasing the amount of use, even if the amount of use is increased, excessive air entrainment and abnormal setting retardation are low, so that the unit water amount can be significantly reduced, which is preferable for producing high-strength concrete. It is preferable to add 0.3% by mass to 1.0% by mass of the water reducing agent in order to reduce the viscosity of the concrete.

[0026] The strength of the surface layer 10 is 1N / mm 2 ~10N / mm 2 In addition, in compressive strength tests, mortar containing PVA does not break even when deformed to the upper limit of compressive deformation, and immediately after the load is released, it recovers from deformation like an elastic body. This rapid recovery of deformation means that it can be said to have elastic properties.

[0027] <About the back layer> The back surface layer 20 is preferably formed to a thickness of 4 mm to 25 mm. If the thickness is less than 4 mm, manufacturing is difficult, and if the thickness is more than 25 mm, problems such as the occurrence of cracks due to drying occur.

[0028] The raw materials used for the back layer 20 are preferably sand mortar using mainly fine aggregates such as cement and sand, or CNF mortar using mainly fine aggregates such as cement and sand, and CNF, and may be the same as the raw materials used for the above-mentioned surface layer. By using the same raw materials, it becomes possible to mold them integrally.

[0029] The mixing ratio of CNF to cement is preferably 0.1% by mass to 5.0% by mass. If it is less than 0.1% by mass, there is a disadvantage that the properties of CNF are not fully expressed, and if it is more than 5.0% by mass, there is a disadvantage in terms of increasing strength.

[0030] When producing CNF mortar, it is preferable to add mineral particles. The mineral particles are preferably 1 mm to 4 mm in particle size and preferably contain borosilicate minerals (mainly SiO2, Na2O, and B2O3) as components. By using mineral particles in this particle size range in combination with CNF, high strength is achieved. In addition, by including SiO2 as a component, it is possible to obtain an action and effect similar to that of fly ash.

[0031] The mixing ratio of mineral particles to cement is preferably 2% by mass to 20% by mass. If it is less than 2% by mass, there is a disadvantage such as a decrease in strength, and if it is more than 20% by mass, there is a problem such as the occurrence of cracks due to alkali-silica reaction.

[0032] The strength of the back layer is 5N / mm according to the compression strength test (JIS A 1108). 2 ~30N / mm 2 It is preferable that:

[0033] <About the void layer> The void layer 30 is made of a layered body 31 covered on both the front and back sides with laminated sheets 32 and 33, and many voids are formed in the layered body 31. The layered body 31 is preferably one that has strength in the thickness direction to such an extent that the internal voids are not crushed when embedded, and examples of such well-known materials include a cardboard material in which many voids are arranged along the surface direction between both sides, and a core material in which many tubular parts penetrating in the thickness direction are connected. Fig. 2 is an external perspective view of the core material, and Fig. 3 is a partially enlarged cross-sectional view of a sound-absorbing panel material using the core material.

[0034] The thickness of the layered body is preferably 5 mm to 40 mm, and the sound absorption characteristics can be changed by changing the porosity of the air gap layer by expanding the internal air gap in the thickness direction. The layered body 31 may be formed by laminating multiple sheets of material, and the thickness can be adjusted appropriately depending on the required sound absorption characteristics.

[0035] The porosity of the air gap layer can be determined by measuring the air gaps in the material used, calculating the volume of the air gap, and then calculating the ratio to the volume of the entire panel material.By setting the porosity to 5% to 45%, it is possible to improve the sound absorption characteristics in the low to mid frequency range.

[0036] The laminated sheets 32 and 33 covering both sides of the layered body 31 can be any film-like material having a blocking function to prevent the cement mixture from entering the inside of the layered body 31. For example, by using a known air bubble sheet, it is possible to form voids as well as a blocking function. The air bubble sheet is a film-like sheet in which air is sealed in a number of protruding voids, and can be made of synthetic resin and used as a buffer sheet. A representative example is one manufactured by adhering a cap film with a number of projections and recesses to a base film. The protruding voids in which air is sealed are preferably set to a diameter of 5 mm to 20 mm and a height of 1 mm to 10 mm. The interval between the protruding voids is preferably set narrower than the interval between the small holes 40, specifically, 1 mm to 5 mm.

[0037] <About small holes> The numerous small holes 40 extending from the surface layer 10 to the layered body 31 of the air gap layer 30 preferably have a hole diameter of 2 mm to 4 mm, with holes smaller than 2 mm resulting in insufficient sound absorbing effect, and holes larger than 4 mm resulting in reduced strength of the sound absorbing panel material. The small holes are formed so as to be distributed over the entire surface layer 10, and are preferably formed so as to be drilled in a direction perpendicular to the surface, and the sound absorbing characteristics can be improved by forming small holes in various directions and depths in accordance with the inclination of the surface.

[0038] The more holes formed, the better in terms of the sound absorbing effect, but it is preferable to set the number of holes to a level that does not affect the strength of the sound absorbing panel material. Also, by making the small holes 40 communicate with all the voids in the layered body 31, the void layer communicates with the outside through the small holes, improving the sound absorbing characteristics.

[0039] Fig. 4 is a partially enlarged cross-sectional view of another embodiment of a sound-absorbing panel material using a cardboard material, Fig. 5 is a partially enlarged cross-sectional view of another embodiment of a sound-absorbing panel material using a core material, and Fig. 6 is an external perspective view of the other embodiment. In the example shown in Fig. 4, a wavy uneven shape 11 is formed on the surface of the surface layer of the sound-absorbing panel material 1 shown in Fig. 1, and in the example shown in Fig. 5, a wavy uneven shape 11 is formed on the surface of the surface layer of the sound-absorbing panel material shown in Fig. 3. The uneven shapes 11 are formed and arranged at equal intervals in a direction along one side of the rectangular sound-absorbing panel material 1' as shown in Fig. 6.

[0040] The unevenness 11 formed on the surface is preferably set so that the height of the convex portions is about 10 mm and the distance between the apexes is about 30 mm. The shape and size of the unevenness 11 affect the sound absorption characteristics in the high frequency range, so they may be set according to the desired sound absorption characteristics. The small holes 40 are preferably formed in a direction almost perpendicular to the surface in accordance with the inclination of the surface, and by forming the small holes evenly at the inclined and bottom positions of the unevenness 11, the sound absorption characteristics for the sound reflected off the surface can be improved by the small holes in different directions.

[0041] Fig. 7 is an explanatory diagram of the manufacturing process of the sound-absorbing panel material. First, a layer that will become the back layer 20 is formed. In this example, sand mortar is used for the back layer. Sand mortar can be made by adding water, sand and admixtures to cement and kneading the mixture. The resulting kneaded mixture is poured into a formwork 100 to form a uniform layer of a specified thickness (Fig. 7(a)).

[0042] When using CNF mortar as the back layer, the mortar can be prepared by adding water and admixtures to the CNF and kneading the mixture, then adding cement and mineral particles and kneading the mixture again.

[0043] Next, the layers that will become the gap layer 30 are laminated. In this example, a structure that will become the gap layer 30 is prepared in advance by using cardboard material as the layered body and bonding it so that both sides are entirely covered with air bubble sheets, and the structure is placed on the top surface of the layer that will become the back surface layer 20 (FIG. 7(b)).

[0044] Next, a layer that will become the surface layer 10 is laminated. In this example, PVA mortar is used for the surface layer. PVA mortar can be made by adding water and admixtures to PVA, kneading, then adding cement and kneading again, and then adding CNF and kneading. The resulting kneaded mixture is poured into a formwork 100, filling the periphery of the structure, and laminating a uniform layer of a predetermined thickness on the upper surface (FIG. 7(c)). Then, a cover plate 101 is placed and fixed on the upper surface of the formwork 100, and hardened in air for about half a day (FIG. 7(d)). In the semi-hardened state, the semi-hardened body is removed from the formwork 100, and small holes that reach all the voids in the cardboard material of the void layer 30 are formed at predetermined intervals by drilling vertically with a drilling machine such as an electric drill (FIG. 7(e)). After that, the material is cured in air in accordance with JIS A 1132 to harden it, and a sound-absorbing panel material is obtained. The obtained sound-absorbing panel material has a structure in which a large number of small holes 40 are formed in the front layer 10 and no small holes are formed in the back layer 20.

[0045] When manufacturing another sound-absorbing panel material shown in FIG. 4 or FIG. 5, the layers that will become the surface layer 10 are laminated and then semi-cured in the air. A part of the kneaded material that will become the surface layer 10 is poured into the grooves of a corrugated formwork in advance and semi-cured in the air. The corrugated formwork can be formed, for example, by cutting a commercially available corrugated sheet to a predetermined size. The corrugated layer that has been semi-cured is laminated and integrated on the upper surface of the layer that will become the surface layer 10, and then in the semi-cured state, holes are drilled in the surface of the surface layer 10 in an almost vertical direction using a drilling machine such as an electric drill, and small holes that reach the void layer are formed at predetermined intervals. The depth of the drilling is set to be deeper than the thickness of the surface layer so as to reach all the voids in the layered body of the void layer. After forming a large number of small holes at predetermined intervals, a hardening treatment is performed by air curing in accordance with JIS A 1132 to obtain a sound-absorbing panel material.

[0046] A sound-absorbing panel structure can be constructed by arranging the obtained sound-absorbing panel materials in a planar shape. By adjusting the presence or absence of unevenness in the surface layer of the sound-absorbing panel material and the porosity of the void layer, it is possible to manufacture multiple types of sound-absorbing panel materials with different sound-absorbing properties, and by appropriately combining and arranging such sound-absorbing panel materials with different sound-absorbing properties, a sound-absorbing panel structure that can handle a wide range of frequencies can be constructed.

[0047] In addition, by using PVA mortar for the surface layer of the sound-absorbing panel material, it is possible to reduce the weight compared to commonly used sand mortar, making it possible to obtain a lightweight sound-absorbing panel structure.In addition, since sand mortar or CNF mortar is used for the back layer of the sound-absorbing panel material and is integrated with the PVA mortar of the surface layer, it is possible to provide the strength and durability required for a structural material, making it possible to realize a practical sound-absorbing panel structure. EXAMPLES

[0048] <About characteristic tests> The following tests were carried out as characteristic tests.

[0049] Sound absorption test (based on JIS A 1409) The sound absorption test was carried out at the Fukui Prefectural Industrial Technology Center (Fukui City, Fukui Prefecture) in a reverberation room constructed within the center, using a steady sound pressure generator (manufactured by Spectris Co., Ltd.) and a sound intensity measuring device (manufactured by Spectris Co., Ltd.).

[0050] Test pieces measuring 35cm long x 35cm wide x 2cm or 4.5cm thick were prepared and laid flat in three pieces vertically and horizontally on the floor of the reverberation room with the surface side facing up to form a sound-absorbing panel structure. The gaps between the test pieces were sealed with commercially available vinyl tape. Four rafters were placed around the periphery of the sound-absorbing panel structure on which the test pieces were arranged, and the gaps between the test pieces and the sound-absorbing panel structure were sealed with vinyl tape.

[0051] A steady-state sound pressure generator was placed 1m above the center of the sound-absorbing panel structure on which the test specimens were arranged, and an acoustic intensity measuring device was placed at a specified position. Then, sound waves of a specified intensity were emitted from the steady-state sound pressure generator toward the sound-absorbing panel structure, and the intensity of the sound reflected by the sound-absorbing panel structure was measured with the acoustic intensity measuring device. The frequency of the sound waves was changed to measure the intensity of the reflected sound, and the sound absorption coefficient for each was calculated. The sound absorption coefficient α was calculated based on the following formula. α(%)=(A / S)×100 where S is the area of ​​the sound absorbing panel structure (m 2 ), A is the equivalent sound absorption area (m2) calculated by the following formula 2 ). A = 55.3 × (V / c) × (1 / T2-1 / T1) c is the speed of sound in air (m / s), V is the volume of the reverberation chamber without the test specimen installed (m 3 ), T1 is the reverberation time (s) in the reverberation chamber when no test specimen is installed, and T2 is the reverberation time (s) in the reverberation chamber when a test specimen is installed.

[0052] ○ Bending strength test (based on JIS A 1106) Immediately after curing, the specimens were subjected to bending strength tests using an Amsler compression tester (manufactured by Technoenami Co., Ltd.; model: Amsler compression tester, 1000 kN). The fracture energy (kNm / m), defined as the area of ​​the bending deflection curve obtained by the bending strength test, was calculated. 2 ) was calculated.

[0053] <Ingredients used> The following materials were prepared as ingredients for the various mortars: Ordinary Portland cement (manufactured by Taiheiyo Cement Corporation) (density 3.16g / cm 3 , specific surface area 3330cm 2 / g) (Mineral composition: C3S 56%, C2S 18%, C3A 9%, C4AF 9%) Cellulose nanofiber (CNF) CNF (Nanoforest-S manufactured by Chuetsu Pulp Industry Co., Ltd.) Produced by the ACC method. Fiber width 20nm or less, CNF concentration 2% Polyvinyl alcohol (PVA) PVA (Fujifilm Wako Pure Chemical Industries, Ltd. polyvinyl alcohol PVA1500; degree of polymerization approximately 1500) Mineral grains (Chie Brazilian shawl tourmaline, grain size 1-4mm, density 3.18g / cm 3 degree) According to the sales materials, it is described as a borosilicate mineral grain containing silicates of sodium, calcium, magnesium, iron, manganese, aluminum, etc. Fine aggregate (manufactured by Nakanihon Gravel Co., Ltd.) (Maximum aggregate size: 2 mm, surface dry density: 2.63 g / cm 3 )

[0054] <About admixtures> The following admixtures were used: ○High-performance water reducing agent (BASF Japan Ltd.; Masterglenium SP8HU)

[0055] <About mixing water> Tap water (Echizen City Waterworks Bureau; hardness 23 mg / liter) was used.

[0056] <About structural materials that form the gap layer> Cardboard material A commercially available 5 mm thick cardboard sheet was cut to the desired size and used. Core material A paper roll core sheet (thickness 10 mm, cell size 14 mm) manufactured by Shin-Nihon Feather Core Co., Ltd. was cut to the desired size and used. 〇Bubble sheet Petit Sheet (registered trademark) manufactured by Kawakami Sangyo Co., Ltd. (projection diameter 10 mm, height 1 mm and 2 mm, projection spacing 1 mm)

[0057] [Example 1] A cement sound-absorbing panel material with a three-layer structure similar to that shown in Figure 1 was fabricated.

[0058] <CNF mortar composition for back layer> The raw materials used were prepared in the following unit amounts: Cement: 1198kg / m 3 CNF: 616kg / m 3 (CNF amount; 12.32kg / m 3 , cement ratio: 1.0% by mass Mineral grains: 34kg / m 3 (cement ratio: 2.8% by mass) Admixture: 35.94kg / m 3

[0059] <PVA mortar composition for surface layer> The raw materials used were prepared in the following unit amounts: Cement: 1093kg / m 3 Water; 565kg / m 3 CNF; 18kg / m 3 (CNF amount; 0.36kg / m 3 , cement ratio: 0.03% by mass PVA: 91 kg / m 3 (cement ratio: 8.3% by mass) Admixture: 32.79kg / m 3

[0060] <About the preparation of test specimens> First, a layer to be the back layer was formed. The CNF mortar was prepared by adding CNF and admixtures to cement, kneading for 5 minutes, then adding mineral particles and kneading for 5 minutes. The resulting mixture was poured into a formwork (35 cm long x 35 cm wide x 2 cm high) to form a uniform layer with a thickness of about 4 mm. After the CNF mortar was semi-hardened, a bubble sheet for the lower layer (32 cm long x 32 cm wide x 2 mm high) was placed on the top of the CNF mortar. The bubble sheet was placed so that its center was aligned with the center position of the formwork, and the periphery was set to a state where the CNF mortar was exposed with a width of 1.5 cm. A cardboard material (32 cm long x 32 cm wide x 5 mm high) and a bubble sheet for the upper layer (same size as the lower layer) were layered on the top of the bubble sheet for the lower layer.

[0061] Next, a layer that would become the surface layer was formed. The PVA mortar was prepared by adding water and admixtures to PVA, kneading for 5 minutes, then adding cement and kneading again for 5 minutes, and then adding CNF and kneading for 5 minutes to produce a kneaded product. The kneaded product obtained was poured into the formwork up to the top surface and formed uniformly to a thickness of about 7 mm. Then, a cover plate was placed on the top surface of the formwork and fixed, and the material was allowed to harden for about half a day, after which it was demolded to obtain a semi-hardened body. The surface of the surface layer of the semi-hardened body was drilled vertically with a commercially available electric drill (drill diameter 3 mm), and small holes were formed that penetrated the surface layer and communicated with all the voids in the cardboard material of the void layer. Small holes were formed on the entire surface at intervals of about 1.5 cm.

[0062] The semi-hardened body with the small holes formed was subjected to air curing in accordance with JIS A 1132 to obtain a hardened test specimen. The obtained test specimen (sound-absorbing panel material) was 35 cm long x 35 cm wide x 2 cm high, had 530 small holes (approximately 3 mm in diameter and 13 mm in length) formed in the surface layer, and had a density of 1.36 g / cm. 3 The porosity was about 8%.

[0063] [Example 2] A cement sound-absorbing panel material having the same three-layer structure as shown in FIG.

[0064] <About the preparation of test specimens> A semi-hardened body was formed by laminating the back layer, the void layer, and the surface layer in a formwork in the same manner as in Example 1. A corrugated body was prepared by cutting a commercially available polyvinyl chloride corrugated sheet (with a peak height of about 10 mm) into a size of 30 cm length x 30 cm width, and the same PVA mortar as that for the surface layer was poured into one side of the corrugated body and semi-hardened in the air to form a corrugated layer, which was then laminated on the top surface of the semi-hardened body to be integrated.

[0065] The corrugated surface of the semi-hardened body was drilled with an electric drill in the same manner as in Example 1 to form small holes penetrating the surface layer and communicating with all the voids in the cardboard material of the void layer. The small holes were formed over the entire surface at intervals of about 1.5 cm.

[0066] The semi-hardened body with the small holes formed was subjected to air curing in accordance with JIS A 1132 to obtain a hardened test specimen. The obtained test specimen (sound-absorbing panel material) was 35 cm long x 35 cm wide x 2 cm high, had 510 small holes (approximately 3 mm in diameter and 7 mm to 25 mm in length) formed in the surface layer, and had a density of 1.54 g / cm. 3 The porosity was about 10%.

[0067] [Example 3] A cement sound-absorbing panel material having a structure similar to the three-layer structure shown in Fig. 4 was produced by increasing the number of cardboard sheets used in the gap layer using the same materials as in Example 2. Specifically, a laminate with two cardboard sheets for the gap layer was produced.

[0068] <About the preparation of test specimens> Using a formwork (length 35 cm × width 35 cm × height 2 cm), a layer of 4 mm thick was formed with CNF mortar as a back layer in the same manner as in Example 2, and a bubble sheet for the lower layer, two sheets of cardboard material, and a bubble sheet for the upper layer were sequentially placed, and a layer of PVA mortar was formed as a surface layer to a thickness of 4 mm, and the layer was hardened for about half a day to obtain a semi-hardened body with a thickness of 20 mm. Then, as in Example 2, the semi-hardened corrugated layers (height 10 mm) were stacked and integrated, and then approximately the same number of small holes (diameter about 3 mm, length 14 to 31 mm) were formed with an electric drill, and the semi-hardened body with the small holes was subjected to air curing in accordance with JIS A 1132 to obtain a hardened specimen. The density was 1.47 g / cm 3 The porosity was about 25%.

[0069] [Example 4] A cement sound-absorbing panel material having a structure similar to the three-layer structure shown in Fig. 4 was produced by increasing the number of cardboard sheets used in the gap layer using the same materials as in Example 2. Specifically, a laminate of five cardboard sheets was produced for the gap layer.

[0070] <About the preparation of test specimens> Using a formwork (length 35 cm x width 35 cm x height 4.5 cm), as in Example 2, a layer of 8 mm thick was formed with CNF mortar as a back layer, and a bubble sheet for the lower layer, five sheets of cardboard material, and a bubble sheet for the upper layer were sequentially placed, and a layer of PVA mortar was formed as a surface layer to a thickness of 8 mm, and the layer was hardened for about half a day to obtain a semi-hardened body with a thickness of 45 mm. Then, as in Example 2, the semi-hardened corrugated layers (height 10 mm) were stacked and integrated, and then approximately the same number of small holes (diameter about 3 mm, length 11 to 60 mm) were formed with an electric drill, and the semi-hardened body with the small holes was subjected to air curing in accordance with JIS A 1132 to obtain a hardened specimen. The density was 1.29 g / cm 3 The porosity was about 35%.

[0071] [Example 5] A cement sound-absorbing panel material having the same structure as the three-layer structure shown in FIG. 5 was produced using the same materials as in Example 2, but using a core material instead of the cardboard material used for the gap layer.

[0072] <About the preparation of test specimens> Using a formwork (length 35 cm × width 35 cm × height 2 cm), a layer of 4 mm thick was formed with CNF mortar as a back layer in the same manner as in Example 2, and a bubble sheet for the lower layer, a core material (thickness 10 mm), and a bubble sheet for the upper layer were sequentially placed, and a layer of PVA mortar was formed as a surface layer to a thickness of 4 mm, and the layer was hardened for about half a day to obtain a semi-hardened body with a thickness of 20 mm. Then, as in Example 2, the semi-hardened corrugated layers (height 10 mm) were stacked and integrated, and then approximately the same number of small holes (diameter about 3 mm, length 6 mm to 32 mm) were formed with an electric drill, and the semi-hardened body with the small holes was subjected to air curing in accordance with JIS A 1132 to obtain a hardened specimen. The density was 1.38 g / cm 3 The porosity was about 25%.

[0073] [Example 6] A sound absorption test was carried out on a sound absorbing panel structure in which a total of nine panels were arranged flat, three by three, using specimens from Example 1 and Example 2. As shown in Fig. 8, the test was carried out on a combination of an arrangement of nine sound absorbing panel materials P1 from Example 1 (Fig. 8(a)), an arrangement of five sound absorbing panel materials P1 from Example 1 and four corrugated sound absorbing panel materials P2 from Example 2 (Fig. 8(b)), and an arrangement of nine corrugated sound absorbing panel materials P2 from Example 2 (Fig. 8(c)). The corrugated sound absorbing panel materials were all arranged so that the corrugated shape was set in the same direction.

[0074] The test results are shown in FIG. 9. FIG. 9 shows a graph plotting the experimental results with the sound absorption coefficient on the vertical axis and the frequency on the horizontal axis. Looking at the low to mid-frequency range (up to 1 kHz) and the mid-to-high frequency range (1 kHz and above), the sound absorbing panel structure shown in FIG. 8(a) shows one peak in the mid-to-high frequency range, and the sound absorbing panel structure shown in FIG. 8(c) shows two peaks in the mid-to-high frequency range. The sound absorbing panel structure shown in FIG. 8(b) shows one peak in the mid-to-high frequency range, and the overall sound absorption coefficient is improved and leveled out compared to the sound absorbing panel structures shown in FIG. 8(a) and (c). Therefore, by combining sound absorbing panel materials with different sound absorbing characteristics, it is possible to suppress frequency dependency and improve the sound absorbing characteristics throughout the low to high frequency range. Specifically, sound absorbing characteristics leveled out in the frequency range of 800 Hz to 1.6 kHz are realized.

[0075] [Example 7] A sound absorption test was carried out on a sound absorbing panel structure in which a total of nine pieces were arranged flat, three pieces each in the vertical and horizontal directions, using the specimens of Examples 3, 4 and 5. The nine sound absorbing panel materials of Examples 3 to 5 were arranged as shown in Fig. 8(c) for the test.

[0076] The test results are shown in Figure 10. Figure 10 shows a graph in which the experimental results are plotted with the sound absorption coefficient on the vertical axis and the frequency on the horizontal axis. Looking at the low to mid-frequency range (up to 1 kHz) and the mid-to-high frequency range (1 kHz and above), the sound-absorbing panel structures in which the sound-absorbing panel materials of Examples 3 to 5 are arranged show one peak in the low to mid-frequency range, and Example 3 also shows one peak in the mid-to-high frequency range. Therefore, by combining sound-absorbing panel materials with different sound-absorbing properties, it is possible to suppress frequency dependency and improve sound-absorbing properties throughout the entire low to mid-frequency range.

[0077] Regarding the test results shown in Examples 1 to 5, when attention was paid to the relationship between the peak frequency at which the maximum sound absorption coefficient was achieved and the void ratio, the results were as follows. Porosity Peak Frequency 8% 1.25kHz (Example 1) 10% 1kHz (Example 2) 25% 500Hz (Example 3) 25% 500Hz (Example 5) 35% 250Hz (Example 4) As the porosity increases, the peak frequency tends to shift to the lower frequency range, with a porosity of 10% being 1 kHz, at 25% being 500 Hz, and at 35% being 250 Hz. By adjusting the porosity of the sound-absorbing panel material based on this knowledge, it is possible to obtain a sound-absorbing panel structure that can handle a wide frequency range.

[0078] [Example 8] A sound absorption test was conducted on the sound absorbing panel structure in which a total of nine panels, three each in the vertical and horizontal directions, were arranged flat using the specimens from Examples 2 to 5. The test was conducted on a combination of five sound absorbing panel materials from Example 2 and four sound absorbing panel materials from Examples 3 to 5 arranged as shown in Figure 8(b). The corrugated sound absorbing panel materials were all arranged so that the corrugated shapes were set in the same direction.

[0079] The test results are shown in FIG. 11. FIG. 11 shows a graph plotting the experimental results with the sound absorption coefficient on the vertical axis and the frequency on the horizontal axis. In the low to mid-frequency range (up to 1 kHz) and the mid to high frequency range (1 kHz or more), the sound absorption panel structure of any combination shows a leveling out in the range from 500 Hz to 1 kHz in the low to mid-frequency range. In addition, in the sound absorbing panel structure in which the sound absorbing panel materials of Examples 2 and 4 are combined and arranged, two peaks appear in the low to mid-frequency range. Therefore, by combining sound absorbing panel materials with different sound absorbing properties, it is possible to suppress frequency dependency and improve the sound absorbing properties throughout the low to mid-frequency range. Specifically, sound absorbing properties that are leveled out in the frequency range of 500 Hz to 1.6 kHz are realized.

[0080] [Example 9] A bending strength test was carried out on the sound-absorbing panel materials of Examples 1 to 5. The bending test results showed that the bending breaking load (kN), maximum strain (mm) and breaking energy (kNm / m 2 In Example 1, 2and in Example 2, 0.3 kN, 2.2 mm and 0.04 kNm / m 2 and in Example 3, 0.2 kN, 2.5 mm and 0.03 kNm / m 2 In Example 4, the values ​​were 0.6 kN, 9.0 mm, and 0.2 kNm / m 2 and in Example 5, 0.3 kN, 7.2 mm and 0.1 kNm / m 2 It was confirmed that both materials had the strength required for construction panels.

[0081] [Example 10] The reverberation time was measured during the above-mentioned sound absorption test for a sound absorbing panel structure in which three test pieces from each of Examples 2 and 4 were arranged vertically and horizontally, and for a sound absorbing panel structure in which five sound absorbing panel materials from Example 2 and four sound absorbing panel materials from Example 4 were arranged as shown in Figure 8(b). The measurement results are shown in Figure 12.

[0082] In Fig. 12, a graph is shown in which the measurement results are plotted with the reverberation time (seconds) on the vertical axis and the frequency on the horizontal axis. For comparison, the measurement results for "no sample" where no sound-absorbing panel structure is arranged are also shown. There is a tendency for the reverberation time to decrease in the case of Example 4 and its combinations, in which the air gap layer of the sound-absorbing panel material is thick, and this is particularly noticeable in the low frequency range.

[0083] As explained above, by combining and arranging sound-absorbing panel materials with different sound-absorbing properties to construct a sound-absorbing panel structure, it is possible to improve the sound-absorbing properties over a wide frequency range, and to realize a sound-absorbing panel structure with reduced frequency dependency. [Industrial Applicability]

[0084] The sound-absorbing panel structure of the present invention is capable of accommodating a wide range of frequencies and its sound-absorbing characteristics can be adjusted to suit the application, making it possible to utilize it as a method of acoustic design. It is expected to be used in a wide range of applications, such as soundproofing measures for low-frequency propeller noise generated by wind power generation, soundproofing measures for buildings and tunnels, and countermeasures for high-frequency vehicle noise on highways. [Explanation of symbols]

[0085] 1 sound-absorbing panel material, 10 surface layer, 11 uneven shape, 20 back layer, 30 gap layer, 31 layered body, 32, 33 laminated sheet, 40 small hole, 100 formwork, 101 cover plate

Claims

1. A sound-absorbing panel structure in which a plurality of sound-absorbing panel materials are arranged, the sound-absorbing panel material having a surface layer made of cement containing polyvinyl alcohol and cellulose nanofibers, a back layer made of cement or cement containing cellulose nanofibers, a void layer arranged so as to be laminated between the surface layer and the back layer, and configured by covering the surface and back sides of a layered body in which a plurality of voids are formed with a laminated sheet, and a plurality of small holes formed from the surface layer to reach the void layer and communicate with all of the voids, wherein the sound-absorbing panel structure has an arrangement of a plurality of types of sound-absorbing panel materials having different sound-absorbing characteristics.

2. The sound-absorbing panel structure according to claim 1 , wherein the surface layer is made of mortar containing polyvinyl alcohol and cellulose nanofibers, and the back layer is made of mortar or mortar containing cellulose nanofibers.

3. The sound-absorbing panel structure according to claim 1 or 2, wherein a plurality of types of the sound-absorbing panel materials having different void ratios in the void layer are arranged.

4. 3. The sound-absorbing panel structure according to claim 1, wherein a plurality of projections and recesses are formed at predetermined intervals along a predetermined direction on the surface of at least a portion of the sound-absorbing panel material.

5. 3. The sound-absorbing panel structure according to claim 1, wherein the layered body is made of cardboard material, and the small holes communicate with all voids in the cardboard material.

6. 3. The sound-absorbing panel structure according to claim 1, wherein the layered body is made of a core material having a number of cylindrical portions connected together and penetrating in the thickness direction, and the small holes are connected to all of the cylindrical portions.

7. 3. The sound-absorbing panel structure according to claim 1, wherein the laminated sheet is a bubble sheet having a large number of voids filled with air.

8. 3. The sound-absorbing panel structure according to claim 1, having sound-absorbing characteristics that are leveled in the frequency range of 500 Hz to 1.6 kHz.

Citation Information

Patent Citations

  • Sound-absorbing panel

    JP1999107225A

  • Sound absorbing structure

    JP2010229737A

  • Noise barrier

    JP2016143049A

  • Cement sound absorbing material

    JP6910678B1

  • Staircase structure with concrete structural members in the step area

    JP7208692B1